2016
DOI: 10.14238/sp8.1.2006.16-24
|View full text |Cite
|
Sign up to set email alerts
|

Penurunan Penggunaan Antibiotik pada Pasien Anak dengan Demam

Abstract: Latar belakang

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 4 publications
0
10
0
1
Order By: Relevance
“…A total of 13 reports reported data on the effect of AMS interventions, of which 11 in hospitals, 23,28,31,33,47,[86][87][88][89][90][91] 1 in primary care, 92 and 1 in community pharmacies 93 (Table 2). Twelve reports used a pre-post design, and one was a randomized controlled trial.…”
Section: Antibiotic Stewardship Interventionsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 13 reports reported data on the effect of AMS interventions, of which 11 in hospitals, 23,28,31,33,47,[86][87][88][89][90][91] 1 in primary care, 92 and 1 in community pharmacies 93 (Table 2). Twelve reports used a pre-post design, and one was a randomized controlled trial.…”
Section: Antibiotic Stewardship Interventionsmentioning
confidence: 99%
“…23,31,47,86,88,90,91 Studies that evaluated education and/or training interventions (5 reports) reported mixed effects on antibiotic consumption and prescribing appropriateness. 31,[87][88][89]92 The one study that evaluated antibiotic restriction with pre-approval found that consumption of restricted antibiotics decreased and of unrestricted narrow-spectrum antibiotics increased. 28 The one randomised study that evaluated the effect of a pharmacist counselling session of outpatient antibiotic users in community pharmacies found that self-reported antibiotic adherence was 311 significantly higher in the intervention group compared to the control group.…”
Section: Antibiotic Stewardship Interventionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Penggunaan antibiotika dinilai dengan melihat rekam medis pemberian antibiotika dan rekam medis pasien dengan mempertimbangkan kesesuaian diagnosis (gejala klinis dan hasil laboratorium), indikasi, regimen dosis, keamanan dan harga. 6,7 Berild dkk.meneliti penurunan penggunaan dan biaya antibiotika dengan penerapan pedoman penggunaan antibiotika di Rumah Sakit Universitas Aker di Oslo, Norwegia. Pada penelitian ini digunakan suatu pedoman yang digunakan untuk sebagai dasar pemakaian antibiotika untuk terapi dan profilaksis.Dari penelitian ini didapatkan penurunan yang signifikan yaitu sebanyak 11% penggunaan antibiotika selama dua tahun penelitian dilakukan.Penggunaan antibiotika spektrum luas menurun sebanyak 23%.…”
unclassified